Plasmodium vivax infection causes acute respiratory distress syndrome: a case report - Gupta, Himanshu; Afsal, Mohammed P; Shetty, Seema M; Satyamoorthy, Kapaettu; Umakanth, Shashikiran (The Journal of Infection in Developing Countries, 2015)
Plasmodium falciparum (Pf) is associated with numerous complications and high mortality, whereas Plasmodium vivax (Pv) infection is generally considered to be benign. However, severe complications, such as acute respiratory distress syndrome (ARDS) in Pv infection, are emerging. This case report highlights the complication of ARDS during the course of Pv infection in a 60-year-old woman. The diagnosis of the patient was made using microscopy, immunochromatography, and polymerase chain reaction assays for Pf and Pv species. The data indicated the presence of mono-Pv infection in the patient’s blood, and Pf infection was specifically ruled out. The patient was discharged after intensive supportive care and antimalarial treatment. Pv infection is associated with ARDS and other complications such as sepsis and multi-organ dysfunction syndrome; this enhanced severity of Pv infection, if unrecognized, can lead to more deaths in malaria-endemic areas.